2017
DOI: 10.1002/hon.2458
|View full text |Cite
|
Sign up to set email alerts
|

Description of late onset neutropenia in indolent lymphoma patients treated with bendamustine plus rituximab

Abstract: Bendamustine (B) associated with rituximab (R) is widely described in literature for the management of patients with chronic lymphoid leukaemia (CLL) and indolent non-Hodgkin lymphoma. Safety data regarding late hematotoxicity such as late onset neutropenia (LON) are scarce. The aim of our study was to assess the incidence and to identify risk factors for LON in patients with indolent non-Hodgkin lymphoma and CLL treated with B and R (B-R). One hundred forty five patients were treated with B-R as first or seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Of these, one had a history of recurrent neutropenia since a treatment of obinutuzumab and bendamustine with an occasional need of G-CSF stimulation. 29 Another patient had declining neutrophils entering the trial with nadir and normalization shortly after inclusion and one patient had neutropenia during a major infection alongside with rituximab treatment.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…Of these, one had a history of recurrent neutropenia since a treatment of obinutuzumab and bendamustine with an occasional need of G-CSF stimulation. 29 Another patient had declining neutrophils entering the trial with nadir and normalization shortly after inclusion and one patient had neutropenia during a major infection alongside with rituximab treatment.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…Most cases of R-induced LON are self-limiting and resolve without any complications (23,24). Although R-induced LON has the potential to be a long-lasting complication, neutrophil recovery with the use of G-CSF usually occurs in as few as four days (4,8,25). In the Verriere et al series, it was not observed an increased infection rate related to LON, and the majority of the patients recover without stimulating agents.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Verriere B et al. described an incidence of 7% of grade III/IV LON in a series of 145 patients with chronic lymphocytic leukemia and NHL treated with RB ( 8 ). Beak et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations